Effects of a handwashing intervention package on handwashing in preschool children. (19th July 2019) - Jess, Rachel L.; Dozier, Claudia L.; Foley, Elizabeth A.
Abstract : Young children who attend out‐of‐home care (e.g., preschool) are more susceptible to infections than children who do not attend out‐of‐home care. Previous research suggests handwashing is effective in reducing risk of infection and illness. However, research suggests that individuals do not routinely wash their hands using methods that healthcare agencies, such as the Centers for Disease Control and Prevention, have determined best practice. We evaluated the effects of a multicomponent handwashing intervention package on correct handwashing across groups of preschool children. Furthermore, we measured the degree to which their hands were clean using premeasures and postmeasures. Results suggest the intervention package was effective at increasing both correct handwashing and cleanliness of participants' hands.